Kennedy’s Disease – Current State Of Knowledge - Dąbrowska, Gabriela Helena; Centkowska, Anna; Wagner-Bieleń, Natalia Katarzyna; Zwierzchowska, Martyna; Antoniak, Agata; Jocz, Anna Maria; Banaśkiewicz, Joanna Karina; Żyta, Aleksandra Maria; Żmijewska, Maria Anna; Ziółkowski, Jakub (Quality in Sport, 2025)
Introduction: Spinal and bulbar muscular atrophy (SBMA), also known as Kennedy’s disease, is a rare X-linked neuromuscular disorder primarily affecting lower motor neuron. It is caused by a CAG trinucleotide repeat expansion in the androgen receptor gene. SBMA typically presents with late-onset, slowly progressive muscle weakness and atrophy, involving both bulbar and extremity muscles. Diagnosis is frequently delayed, particularly in individuals without a known family history of the disease, with an average diagnostic lag of approximately five years. Purpose: This paper aims to analyze and synthesize the current state of knowledge on SBMA spanning early clinical presentation, diagnostic processes, management of multifaceted symptoms, and emerging therapeutic strategies. Methodology: The PubMed and Google Scholar database were searched for scientific articles published between 2015-2024 where ‘Spinal and bulbar muscular atrophy’, ‘Kennedys disease’ appears as keywords. Conclusion: SBMA clinically presents with progressive muscle weakness, bulbar dysfunction, tremor, and metabolic disturbances, often beginning between the ages of 30 and 50. Many patients experience a prolonged and convoluted diagnostic pathway, often involving misdiagnosis and unnecessary or invasive interventions. While no curative treatment currently exists, management focuses on supportive multidisciplinary care, including physical therapy, neurologopedic intervention, and nutritional and respiratory monitoring. Experimental therapies targeting the androgen receptor pathway and molecular mechanisms are under investigation, offering hope for future disease-modifying strategies. Continued research and individualized care remain essential to improving outcomes and quality of life in patients with SBMA.